Convergence of Law and Technology Through Optimization of Pancasila - Franciscus Xaverius Wartoyo; Yuni Priskila Ginting (Journal of Digital Law and Policy, 2022)
Starting from the legal norms in the EIT Law, Pancasila is the source of all the resources needed for technological development in the industrial revolution. In encouraging the optimal use of cyberspace, it must still be based on Pancasila to minimize the pessimistic impact that will arise. This study focuses on looking at the application of the convergence of law and technology in the industrial revolution on victims of cybercrime in terms of the principles of Pancasila. This research is research that requires further examination. The method used is normative juridical. This preliminary research concludes that in the context of the convergence of law and technology in the industrial revolution, it must still be based on the teachings of Pancasila to form cyberspace and human resources as the first step in the convergence of law and technology in the industrial revolution. However, the regulation even though it has the EIT Law does not solve the technical problems in the industrial revolution. Mainly related to the convergence that leads to various forms of new virtual services and various technical problems that continue to develop. Keywords: Convergence of Law, Technology, Pancasila